2019
DOI: 10.1007/s11557-019-01491-5
|View full text |Cite
|
Sign up to set email alerts
|

Rare and undersampled dimorphic basidiomycetes

Abstract: The diversity of yeasts has grown rapidly as the discovery of new species has benefited from intensified sampling and largely improved identification techniques. An environmental study typically reports the isolation of yeast species, some of which are new to science. Rare species represented by a few isolates often do not result in a taxonomic description. Nucleic acid sequences from these undescribed yeasts remain in public sequence databases, often without a proper taxonomic placement. This study presents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 66 publications
(166 reference statements)
0
31
0
Order By: Relevance
“…amylolentus species complex. Our definition of these isolates as species is in accord with previous studies of these and other species in which a limited number of isolates, or a single isolate, was sufficient for defining and naming novel taxa (67, 7678).…”
Section: Discussionmentioning
confidence: 66%
“…amylolentus species complex. Our definition of these isolates as species is in accord with previous studies of these and other species in which a limited number of isolates, or a single isolate, was sufficient for defining and naming novel taxa (67, 7678).…”
Section: Discussionmentioning
confidence: 66%
“…and 1 gap), using TEF1 and RPB1 the number of nucleotide substitutions was considerable – without hits with Heterocephalacria . In compliance with a recent phylogenetic analysis of the genus ( Kachalkin et al 2019 ), the placement of the new species is demonstrated using the combined ITS and LSU rDNA phylogeny. Heterocephalacria septentrionalis can be differentiated from H. sinensis based on its ability to assimilate galactose, maltose, trehalose, melezitose, L-rhamnose, glycerol, D-mannitol, D-glucitol, citric acid, and negative growth on L-sorbose.…”
mentioning
confidence: 87%
“…between strains from Nadym and Kandalaksha) and represented a hitherto undescribed species of Heterocephalacria . The genus Heterocephalacria comprises three sexual mycoparasites of lichens ( H. bachmannii and H. physciacearum ) and mushrooms ( H. solida ), and several asexual species of yeasts ( Kachalkin et al 2019 , Kunthiphun et al 2019 , Li et al 2019 ). Two new yeast strains were isolated as a minor component from Cladonia lichens whose thallus did not have basidioma-like structures.…”
mentioning
confidence: 99%
“…The genus Naganishia comprises a variety of asexually reproducing yeast species with different morphological and physiological characteristics and distinct habitats. Currently, there are 18 species recognized as belonging to the genus Naganishia , including the recently described Naganishia qatarensis , Naganishia nivalis and Naganishia indica [10–12]. The members of the genus Naganishia are characterized by the inability to form basidiocarps, hyphae, pseudohyphae or ballistoconidia.…”
Section: Introductionmentioning
confidence: 99%